Les relations publiques, véritable instrument de démocratie - Bernard Dagenais (Communication)
In all societies, certain organizations defend the status quo and others want to change it. Each will use public relations to make known and defend their different points of view, denounce their adversaries, rectify the remarks which circulate in public and which do not correspond with their ideals. To accomplish this, they are in possession of competencies, time, and resources that none of the media are. In this sense, they exercise a much closer surveillance of the environment than the media do. For emerging organizations, the recourse to certain strategies of communication allow them to overcome a certain resistance, even, in some cases, a certain hostility on the part of society and the media. It is in this sense that public relations constitute a veritable tool of democracy.